Ordinance No. 7, § 1, Bucoda Town Council (1910) (Bucoda, Washington). - (:unkn) unknown (My University, 1910)
.all persons ( except police officers and other persons whose duty it is to execute process or warrants, or make arrests) who shall carry upon his person any concealed weapon, consisting of either a revolver or other firearm or any knife, (other than ordinary pocket knife) or any dirk or dagger, sling shot or metal knuckles, or any instrument by the use of which injury could be inflicted upon the person or property of any other person.All persons (except police officers as aforesaid) who shall draw, exhibit or attempt to use any deadly weapon upon, to or against another person in said town (excepting in necessary defence of person or property) with intent to bodily injure to such person.All persons (except police officers aforesaid and persons practicing at target shooting in a shooting gallery, duly licensed) who shall upon any of the public streets of this town, fire off or discharge any gun, pistol or firearm of any kind, or any bomb
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE